1988
DOI: 10.1111/j.1365-2559.1988.tb01919.x
|View full text |Cite
|
Sign up to set email alerts
|

Basosquamous cell carcinoma of the skin with metastases

Abstract: Two cases of basosquamous cell carcinoma of the skin with lymph node, lung and bone metastases are reported. Metastases occurred 4 and 7 years after identification of the primary tumour. Both the primary and metastatic lesions had areas of typical basal cell carcinoma and squamous cell carcinoma and also intermediate carcinomatous tissue. In the bone metastasis of one case there were rudimentary hair follicles and areas of matrical differentiation. These cases further support the existence of basosquamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
6

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 5 publications
(2 reference statements)
0
8
0
6
Order By: Relevance
“…Several authors have suggested that BSC is a more aggressive tumor. [3][4][5][6] The real question is, "More aggressive than what?" BSC probably has a greater potential for metastasis than BCC since BCC rarely metastasizes, and it probably carries its potential for metastasis in the squamous component.…”
Section: Department Of Dermatology University Of Massachusetts Medicmentioning
confidence: 99%
“…Several authors have suggested that BSC is a more aggressive tumor. [3][4][5][6] The real question is, "More aggressive than what?" BSC probably has a greater potential for metastasis than BCC since BCC rarely metastasizes, and it probably carries its potential for metastasis in the squamous component.…”
Section: Department Of Dermatology University Of Massachusetts Medicmentioning
confidence: 99%
“…Basosquamous carcinoma (BSC) is an uncommon skin cancer entity. As a rare variant or subtype of basal cell carcinoma (BCC), it features characteristics of both BCC (especially histologic characteristics) and squamous cell carcinoma (SCC; mainly clinical behavior) [1] , [2] , [3] , [4] , [5] . First described by MacCormac in 1910 [6] , BSC is a rare tumor with an incidence of less than 2% of all non-melanoma skin cancers and is predominant in men [5] , [7] , [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…As this case study demonstrates, an early diagnosis of BsC is important due to the particularly aggressive nature of the tumour, the increased likelihood of recurrence and the potential for metastasis [1, 7]. In fact, BsC is reported to have greater metastatic potential than SCC [8].…”
Section: Discussionmentioning
confidence: 99%